Gustave Doré - Dante Alighieri - InferNo - Plate 65 (Canto XXXI - The... - Gustave Doré (Wikimedia Commons, 1857)
Notice iconographique issue de Wikimedia Commons. Titre: Gustave Doré - Dante Alighieri - InferNo - Plate 65 (Canto XXXI - The Titans). Gustave Doré's illustrations to Dante's Inferno, Plate LXV: Canto XXXI: The titans and giants. "This proud one wished to make experiment / Of his own power against the Supreme Jove" (Longfellow).
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie